The grammar of expressivity - Gutzmann, Daniel (Oxford : Oxford University Press, 2019)
"This volume provides a detailed account of the syntax of expressive language, that is, utterances that express, rather than describe, the emotions and attitudes of the speaker ... Daniel Gutzmann demonstrates that expressivity has strong syntactic reflexes that interact with the semantic and pragmatic interpretation of these utterances, and argues that expressivity is in fact a syntactic feature on a par with other established features such as tense and gender. Evidence for this claim is drawn from three detailed case studies of expressive adjectives, intensifiers, and vocatives; their puzzling properties are accounted for through a minimalist approach to syntactic features and agreement, which shows that expressivity can partake in agreement operations, trigger movement, and be selected for syntactically. The analysis not only supports the hypothesis of expressive syntax, but also highlights the hidden role that grammar may play in phenomena that are traditionally considered to be solely semantic in nature" -- Publisher.
1. Introduction -- 2. The expressive function of language -- 3. Syntax, features, and agreement -- 4. Expressive adjectives -- 5. Expressive intensifiers -- 6. Expressive vocatives -- 7. Looking back and looking ahead.
Includes bibliographical references (pages 267-280) and indexes.
In English with some German.
Keywords: Emotive (Linguistics); Grammar, Comparative and general -- Syntax; Expression; Language and emotions; Emotions; Emotive (Linguistics); Grammar, Comparative and general -- Syntax; Expression; Emotions; Language and emotions